High-temperature forming limit diagram FLD determination method

By applying high-temperature protective coatings of alumina powder and other components on the mesh surface of the high-temperature forming test sample, the problem of fuzzy grid during the high-temperature forming process is solved, and the time and accuracy of the high-temperature forming limit diagram (FLD) test is improved.

CN119666646AInactive Publication Date: 2025-03-21TANGSHAN IRON & STEEL GROUP +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411645637.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the high-temperature forming process, the generation and fall of the iron oxide sheet on the metal surface of the sample leads to blurred grids and difficult to measure strain, which limits the time and accuracy of the high-temperature forming limit diagram (FLD) test.

Method used

A high-temperature protective coating paint made of aluminum oxide powder, barium borate, binder, etc. is used to apply it to the surface of the sample grid. After curing, high-temperature forming test is carried out. After the test, the coating is cleaned to obtain a clear strain grid.

Benefits of technology

It effectively prevents the grid from oxidizing and eroding in high-temperature tests, ensures clarity of the grid and accurate measurement of strain results after the test, extends the test time and improves the accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119666646A_ABST
    Figure CN119666646A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature forming limit diagram FLD determination method. The method comprises the steps of sample surface strain analysis grid preparation, high-temperature protective coating paint smearing on a sample surface strain analysis grid, high-temperature forming limit testing, high-temperature protective coating cleaning and strain result measurement. Wherein the high-temperature protective coating is prepared from aluminum oxide powder, barium borate, a binder, a stabilizer, a thickener, a preservative and a coloring agent. According to the method disclosed by the invention, clear grid strain information can be obtained from the sample after high-temperature forming, and the problems that the grid is easy to oxidize and fall off in a high-temperature forming test and the grid strain cannot be effectively measured after the test are solved; the method is simple in principle and convenient to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal sheet forming performance and test methods, and in particular relates to a high temperature forming limit diagram (FLD) determination method. Background Art

[0002] With the widespread application of hot-formed steel in automobile bodies, the testing of its high-temperature forming limit diagram (FLD) is becoming more and more common. The drawing of the forming limit diagram (FLD) requires measuring the mesh deformation after the specimen is formed to determine the strain. During the high-temperature forming process, iron oxide scale will be generated on the metal surface of the specimen. The metal surface grid prepared by ordinary photolithography technology or electrochemical corrosion method will become blurred and difficult to measure after the test as the surface iron oxide scale is generated and falls off, which greatly limits the time and test accuracy of the high-temperature forming limit diagram (FLD) test.

[0003] Therefore, it is of great significance for the high-temperature forming limit diagram (FLD) test of metal sheets to find a grid preparation method that can retain the metal surface grid of the specimen during the high-temperature forming process so that the grid strain can be accurately measured after the test. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for determining a high temperature forming limit diagram FLD, which can obtain a clear strain grid and solve the problem that the strain analysis grid is unclear and cannot be measured after the test.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for determining a high-temperature forming limit diagram (FLD), comprising preparing a strain analysis grid on the surface of a sample, applying a high-temperature protective coating on the analysis grid, performing a high-temperature forming limit test, cleaning the high-temperature protective coating and measuring the strain results; wherein the high-temperature protective coating is prepared from alumina powder, barium borate, a binder, a stabilizer, a thickener, a preservative and a colorant.

[0006] Furthermore, the mass percentage of each component in the high temperature protective coating paint of the present invention is: 40-45% alumina powder, 15-25% barium borate, 15-20% binder, 2.5-7.5% stabilizer, 2.5-7.5% thickener, 2.5-7.5% preservative, and 2.5-7.5% colorant.

[0007] Furthermore, the preparation method of the high temperature protective coating paint of the present invention is as follows: according to the ratio of each component in the above coating paint, the aluminum oxide powder and the barium borate are mixed and heated and stirred to dissolve, and then the binder, stabilizer, thickener, preservative and colorant are added in sequence and stirred evenly to obtain the product.

[0008] Furthermore, the pH value of the high temperature protective coating of the present invention is 8-9.

[0009] Furthermore, the method for using the high-temperature protective coating of the present invention is as follows: evenly apply the evenly mixed high-temperature protective coating on the sample grid of the high-temperature forming limit test, cure at room temperature for more than 1 hour, and control the thickness of the high-temperature protective coating to 20-50 microns.

[0010] Preferably, the coating of the present invention has a curing time of 1.5-2 hours. If the time is too short, the curing is incomplete, and if the time is too long, the test progress is affected; the thickness of the coating after curing can be measured by a coating thickness gauge. If the coating is too thin, the high temperature protection effect is poor, and if the coating is too thick, the subsequent cleaning effect is affected.

[0011] Furthermore, the binder of the present invention is a phosphoric acid binder (such as aluminum dihydrogen phosphate) or a silicate binder (such as sodium silicate).

[0012] Furthermore, the stabilizer of the present invention is a calcium / zinc stabilizer.

[0013] Furthermore, the thickener of the present invention is bentonite or diatomaceous earth.

[0014] Furthermore, the preservative of the present invention is a benzimidazole ester fungicide (such as BIT-85) or a 1,2-benzisothiazolin-3-one reagent.

[0015] Furthermore, the colorant of the present invention is a water-based transparent iron oxide color paste.

[0016] Furthermore, the temperature of the high temperature forming limit test of the present invention does not exceed 1100°C.

[0017] Furthermore, the solvent used for cleaning the high-temperature protective coating of the present invention is a mixture of sulfuric acid and anhydrous ethanol; the mass fraction of sulfuric acid in the solvent is 10-25%.

[0018] Furthermore, the sample surface strain analysis grid of the present invention is prepared by photolithography or electrochemical etching, and its parameters are the same as those of the conventional forming limit diagram (FLD) sample grid preparation, and it is necessary to ensure that the grid has a certain depth and is clear.

[0019] Furthermore, before preparing the strain analysis grid of the present invention, the sample surface is cleaned with an organic solvent such as alcohol or acetone to remove grease and impurities on the sample surface, thereby facilitating the subsequent preparation of the grid.

[0020] The method of the invention is applicable to hot-formed steel requiring a high-temperature forming limit diagram (FLD) test and other metal sheets requiring a high-temperature forming limit diagram (FLD) test.

[0021] The method of the present invention has the following beneficial technical effects: The present invention uses a high temperature protective coating to protect the high temperature forming limit diagram (FLD) test sample grid from being oxidized and corroded during the high temperature test. After the test, a clear strain grid is obtained by cleaning the high temperature coating, thereby ensuring the measurement of the strain result. The high temperature protective coating of the present invention can withstand a high temperature of 1100°C and can meet the needs of most metal high temperature forming limit diagram (FLD) tests. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the test sample after the high temperature forming test of Example 1 and the removal of the high temperature protective coating.

[0023] Figure 2 This is the test sample of Comparative Example 1 after high temperature forming test.

[0024] Figure 3 This is the test sample of Example 2 after the high temperature forming test and the removal of the high temperature protective coating.

[0025] Figure 4 This is the test sample of Comparative Example 2 after high temperature forming test.

[0026] Figure 5 This is the test sample after the high temperature forming test of Example 3 and the removal of the high temperature protective coating.

[0027] Figure 6 This is the test sample of Comparative Example 3 after high temperature forming test. DETAILED DESCRIPTION

[0028] In order to clearly describe the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with the accompanying drawings and specific implementation examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Example 1

[0029] The sample material for the high temperature forming limit diagram (FLD) test in this embodiment is 22MnB5 hot-formed steel with a thickness of 1.2 mm, and the sample size is in accordance with the provisions of GB / T 15825.8-2008 Sheet Metal Formability and Test Methods Part 8: Guide to Forming Limit Diagram (FLD) Determination; the high temperature forming limit diagram (FLD) determination method is as follows: (1) Place the sample to be tested in alcohol, use ultrasonic cleaning to remove grease and impurities, and then blow dry with a hair dryer; (2) Prepare a strain analysis grid on one side of the specimen using an electrochemical corrosion method; (3) Preparation of high temperature protective coating: according to the ratio, add aluminum oxide powder and barium borate into a stirrer, heat and stir until dissolved; then add aluminum dihydrogen phosphate binder, calcium / zinc stabilizer, bentonite thickener, BIT-85 preservative, and water-based transparent iron oxide color paste as colorant in sequence, and stir evenly to prepare a high temperature protective coating; the mass percentage of each component in the high temperature protective coating is: aluminum oxide powder 40%, barium borate 15%, aluminum dihydrogen phosphate binder 15%, calcium / zinc stabilizer 7.5%, bentonite thickener 7.5%, BIT-85 preservative 7.5%, and water-based transparent iron oxide color paste as colorant 7.5%.

[0030] The mixed high-temperature protective coating was evenly applied on the strain analysis grid of the high-temperature forming limit test, and cured at room temperature for 1.5 hours. The thickness of the high-temperature protective coating was measured by a coating thickness gauge and was 22 microns. (4) The sample was mounted on a high temperature forming test machine and heated to 850°C for 5 min, followed by a high temperature forming test in accordance with GB / T 15825.8-2008; (5) After the test, the sample surface was cleaned with a mixed solution of sulfuric acid and anhydrous ethanol (the mass fraction of sulfuric acid in the mixed solution was 10%) to remove the high-temperature protective coating, and then the strain grid could be measured.

[0031] The samples of this embodiment were subjected to high temperature forming test, and the test samples after removing the high temperature protective coating were as follows: Figure 1 As shown, the prepared grid can still be clearly displayed after the 850℃ high temperature test, and strain analysis can be easily performed. Comparative Example 1

[0032] The difference between this comparative example and Example 1 is that no high temperature protective coating is applied on the surface of the grid. After the strain analysis grid is prepared, a high temperature test is directly performed. The results are as follows: Figure 2 shown by Figure 2 It can be seen that the mesh prepared by this conventional method is blurred and cannot be used for strain analysis. Example 2

[0033] The sample material for the high temperature forming limit diagram (FLD) test in this embodiment is 30MnB5 hot-formed steel with a thickness of 1.4 mm. The sample size is in accordance with the provisions of GB / T 15825.8-2008 Sheet Metal Formability and Test Methods Part 8: Guide to Forming Limit Diagram (FLD) Determination. The high temperature forming limit diagram (FLD) determination method is as follows: (1) Place the sample to be tested in alcohol, use ultrasonic cleaning to remove grease and impurities, and then blow dry with a hair dryer; (2) Prepare a strain analysis grid on one side of the specimen using an electrochemical corrosion method; (3) Preparation of high temperature protective coating: according to the ratio, add alumina powder and barium borate into a stirrer, heat and stir until dissolved; then add sodium silicate as a binder, calcium / zinc stabilizer, diatomaceous earth as a thickener, 1,2-benzisothiazolin-3-one reagent as a preservative, and water-based transparent iron oxide paste as a colorant in sequence, and stir evenly to prepare a high temperature protective coating; the mass percentage of each component in the high temperature protective coating is: 45% alumina powder, 25% barium borate, 20% sodium silicate as a binder, 2.5% calcium / zinc stabilizer, 2.5% diatomaceous earth as a thickener, 2.5% 1,2-benzisothiazolin-3-one reagent as a preservative, and 2.5% water-based transparent iron oxide paste as a colorant.

[0034] The mixed high-temperature protective coating was evenly applied on the strain analysis grid of the high-temperature forming limit test, and cured at room temperature for 2 hours. The thickness of the high-temperature protective coating was measured by a coating thickness gauge and was 47 microns. (4) Install the sample on a high temperature forming test machine, heat the sample to 1000°C, keep it at this temperature for 5 min, and then conduct a high temperature forming test in accordance with GB / T 15825.8-2008; (5) After the test, the sample surface was cleaned with a mixed solution of sulfuric acid and anhydrous ethanol (the mass fraction of sulfuric acid in the mixed solution was 25%) to remove the high-temperature protective coating, and then the strain grid could be measured.

[0035] The sample of this embodiment was subjected to a high temperature forming test, and the analysis grid after removing the high temperature protective coating was as follows: Figure 3 As shown, the prepared grid can still be clearly displayed after the 1000℃ high temperature test, and strain analysis can be easily performed. Comparative Example 2

[0036] The difference between this comparative example and Example 2 is that no high temperature protective coating is applied on the surface of the grid. After the strain analysis grid is prepared, a high temperature test is directly performed. The results are as follows: Figure 4 shown by Figure 4 It can be seen that the mesh prepared by this conventional method is blurred and cannot be used for strain analysis. Example 3

[0037] The sample material for the high temperature forming limit diagram (FLD) test in this embodiment is 34MnB5 hot-formed steel with a thickness of 1.2 mm, and the sample size is in accordance with the provisions of GB / T 15825.8-2008 Sheet Metal Formability and Test Methods Part 8: Guide to Forming Limit Diagram (FLD) Determination; the high temperature forming limit diagram (FLD) determination method is as follows: (1) Place the sample to be tested in alcohol, use ultrasonic cleaning to remove grease and impurities, and then blow dry with a hair dryer; (2) Prepare a strain analysis grid on one side of the specimen using an electrochemical corrosion method; (3) Preparation of high temperature protective coating: according to the ratio, add aluminum oxide powder and barium borate into a stirrer, heat and stir until dissolved; then add aluminum dihydrogen phosphate binder, calcium / zinc stabilizer, diatomaceous earth thickener, preservative BIT-85, and water-based transparent iron oxide color paste as colorant in sequence, and stir evenly to prepare high temperature protective coating; the mass percentage of each component in the high temperature protective coating is: aluminum oxide powder 42%, barium borate 23%, aluminum dihydrogen phosphate binder 15%, calcium / zinc stabilizer 5%, diatomaceous earth thickener 5%, BIT-85 preservative 5%, and water-based transparent iron oxide color paste as colorant 5%.

[0038] The mixed high-temperature protective coating was evenly applied on the strain analysis grid of the high-temperature forming limit test, and cured at room temperature for 2 hours. The thickness of the high-temperature protective coating was measured by a coating thickness gauge and was 34 microns. (4) The sample was mounted on a high temperature forming test machine and heated to 1050°C for 5 min, followed by a high temperature forming test in accordance with GB / T 15825.8-2008; (5) After the test, the sample surface was cleaned with a mixed solution of sulfuric acid and anhydrous ethanol (the mass fraction of sulfuric acid in the mixed solution was 15%) to remove the high-temperature protective coating, and then the strain grid could be measured.

[0039] The sample of this embodiment was subjected to a high temperature forming test, and the analysis grid after removing the high temperature protective coating was as follows: Figure 5 As shown, it can be seen that the prepared grid can still obtain a clear strain grid after the 1050℃ high temperature test, which can be conveniently used for strain analysis. Comparative Example 3

[0040] The difference between this comparative example and Example 3 is that no high temperature protective coating is applied on the surface of the grid. After the strain analysis grid is prepared, a high temperature test is directly performed. The results are as follows: Figure 6 shown by Figure 6 It can be seen that the mesh prepared by this conventional method is blurred and cannot be used for strain analysis.

Claims

1. A method for determining a high temperature forming limit diagram FLD, characterized in that: It includes the preparation of strain analysis grid on the surface of the sample, application of high-temperature protective coating on the analysis grid, high-temperature forming limit test, high-temperature protective coating cleaning and strain result measurement; wherein the high-temperature protective coating is prepared from alumina powder, barium borate, binder, stabilizer, thickener, preservative and colorant.

2. A method for determining a high temperature forming limit diagram FLD according to claim 1, characterized in that: The mass percentage of each component in the high temperature protective coating is: 40-45% alumina powder, 15-25% barium borate, 15-20% binder, 2.5-7.5% stabilizer, 2.5-7.5% thickener, 2.5-7.5% preservative, and 2.5-7.5% colorant.

3. A method for determining a high temperature forming limit diagram FLD according to claim 1, characterized in that: The preparation method of the high temperature protective coating is as follows: alumina powder and barium borate are mixed, heated and stirred to dissolve, and then a binder, a stabilizer, a thickener, a preservative and a colorant are added in sequence and stirred evenly to obtain the coating.

4. A method for determining a high temperature forming limit diagram FLD according to claim 1, characterized in that: The method of using the high temperature protective coating is as follows: evenly apply the mixed high temperature protective coating on the sample grid of the high temperature forming limit test, cure at room temperature for more than 1 hour, and control the thickness of the high temperature protective coating to be 20-50 microns.

5. A method for determining a high temperature forming limit diagram FLD according to claim 4, characterized in that: The coating curing time is 1.5-2h.

6. A method for determining a high temperature forming limit diagram (FLD) according to any one of claims 1 to 3, characterized in that: The adhesive is a phosphoric acid adhesive or a silicate adhesive.

7. A method for determining a high temperature forming limit diagram FLD according to claim 1, characterized in that: The stabilizer is a calcium / zinc stabilizer; the thickener is bentonite or diatomaceous earth.

8. A method for determining a high temperature forming limit diagram (FLD) according to claim 1, characterized in that: The preservative is a benzimidazole ester fungicide or a 1,2-benzisothiazolin-3-one reagent; and the colorant is a water-based transparent iron oxide color paste.

9. A method for determining a high temperature forming limit diagram (FLD) according to claim 1, characterized in that: The temperature of the high temperature forming limit test does not exceed 1100°C.

10. A method for determining a high temperature forming limit diagram (FLD) according to claim 1, characterized in that: The solvent used for cleaning the high-temperature protective coating is a mixture of sulfuric acid and anhydrous ethanol; the mass fraction of sulfuric acid in the solvent is 10-25%.

Citation Information

Patent Citations

  • Experimental method for building forming limit diagram of transformation induced plasticity steel plate

    CN101598720A

  • Testing device and testing method for establishing high-temperature formed limit diagram of ultrahigh-strength boron steel plate

    CN102156080A

  • Treatment coating capable of improving oxidation resistance of metal piece

    CN110698895A

  • Carbon / carbon composite material surface grid structure enhanced anti-ablation coating as well as preparation method and application thereof

    CN116573953A

  • High-temperature-resistant coating and preparation method thereof

    CN116925581A